RESEPSI MAHASISWA UIN ALAUDDIN MAKASSAR TERHADAP KONTEN DAKWAH CHANNEL YOUTUBE JEDA NULIS (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This study aims to find out the reception of UIN Alauddin Makassar students towards da'wah content on the Jeda Nulis YouTube channel, especially on the Breathless Playlist. Also, to find out the decoding of UIN Alauddin Makassar students on da'wah content on the Jeda Nulis YouTube channel, especially on the Inhale Playlist. This study adopts a qualitative approach by utilizing the reception analysis method from Stuart Hall, to understand the perspective and meaning given by individuals to the phenomenon studied. Data collection is carried out through three main methods, namely direct observation, in-depth interviews, and documentation, in order to obtain comprehensive and detailed information. The main source of data in this study is students from UIN Alauddin Makassar, who were chosen because of their relevance to the research topic The results of this study explain that the reception of UIN Alauddin Makassar students to the da'wah content of the Jeda Nulis YouTube channel, especially on the inhale playlist, is very diverse. This study shows that there are six informants who receive all the content of the message conveyed or it can be said that these six informants are in a dominant hegemonic position. In addition, there are two informants who accept but reject some things in their application or it can be said that these two informants are in a negotiating position. The implications of this study emphasize that da'wah content managers need to pay attention to attractive and creative presentation formats. Videos with good visual elements and a strong narrative supported by the right theme selection tend to be more attractive to students. The da'wah content of the Jeda Nulis YouTube channel has presented this for students.